رموز الأعداد والحروف فى شعر الشيخ الأكبر محيي الدين بن عربي - المولى، عبدالله محمود طه (جامعة الموصل - كلية الآداب, 2007)
Sheikh Muhi-Iddeen Ibn Arabi who died at (638 A. H.) is a Sufi (Islamic Mystic), Philosopher and a great writer. He was born and grown up in Al-Andalus. Then he emigrated to the east. His poetry is predominantly marked with symbolic style who used to serve his mystical philosophical and gnostic way of thinking. symbols of numbers, which are served by Ibn Arabi to support his gnostic way of life. symbols of letters, which made up an important aspect used in a gnositic occupation. Hence, letters refer to the universe and they are the opposite side of it.
Keywords: توحيد الألوهية -- ابن عربي ، محي الدين محمد بن علي بن محمد ، ت 638 هـ -- الشعر العربي -- الفكر الصوفى -- التراث الصوفي -- المذاهب الفقهية -- الفلسفة الإسلامية -- الإيمان بالله -- التصوف الإسلامي